INTEGRATION OF THE CURRICULUM OF LOVE IN MADRASAH THROUGH HUMANISTIC AND MEANINGFUL CHEMISTRY LEARNING - Shorihatul Inayah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This study explores the integration of the Curriculum of Love within madrasah education through the implementation of humanistic and meaningful chemistry learning. The Curriculum of Love emphasizes compassion, empathy, and moral awareness as core values in developing students’ holistic character. Using a qualitative descriptive approach, this research investigates how chemistry learning often viewed as abstract and formulaic can be transformed into a medium for nurturing love for God, humanity, and nature. Data were collected through classroom observations, interviews with teachers, and document analysis. The findings reveal that the integration of love-based values is effectively achieved when teachers design contextual learning experiences that connect chemical concepts with real life moral and environmental issues. Humanistic approaches such as dialogue, reflection, and cooperative learning foster students’ affective engagement, while meaningful learning strategies enhance their understanding and appreciation of chemistry as a manifestation of divine order. The study concludes that embedding the Curriculum of Love within chemistry learning strengthens both cognitive mastery and emotional-spiritual intelligence, supporting the broader goal of madrasah education to produce knowledgeable and compassionate individuals.